HOT COFFEE FOR THE GUEST: GASTRO CRITICISM ON BUDI DARMA'S 'TAMU' - Dipa Nugraha (UIN Raden Mas Said Surakarta, 2021)
Tamu (Guest) is a short story written by one of the most influential writers in Indonesia, Budi Darma. It depicts wedang kopi (hot coffee) serving tradition to guests in Java. Gastro criticism is used to reveal the significance of hot coffee serving in the short story. Close reading method is used to read and analyze the text. From the analysis, the short story reveals not just a tradition in the 1940-1950s of Indonesia on coffee and hospitality but also the effect on a man of the absence of hot coffee in his house when there is a woman in the house. Manggolo, one of the main characters in the story, feels insecure in his own house because he does not get served hot coffee he expects from his daughter-in-law living under the same roof. Furthermore, this research suggests the possibility of combining gastro criticism and gender studies.Â Â